Justice undercover - Queen, Connie (Love inspired suspense., 2020)
"Going undercover as a nanny brings presumed-dead ex-US Marshal Kylie Stone closer to catching the man who murdered the witness in her protection- and also killed Texas Ranger Luke Dryden's sister. When someone tries to kidnap the twins in her care, Kylie must tell their uncle the truth- and convince Luke to help her. But will revealing her identity put all their lives at stake?" --